Kajian Eksperimen Instalasi Pompa Seri dan Paralel Terhadap Efisiensi Penggunaan Energi - Iman Syahrizal; Daud Perdana (Universitas Muhammadiyah Metro, 2019)
The pump is used to transfer liquid fluid from a low place to a high place or from one place to another with a certain distance and with a certain height. This study aims to figure the connection of series and parallel pumps to the discharge, pressure and pump power, and to figure the efficiency of series and parallel pumps with energy use. This study was conducted in a mechanical engineering major at Sambas State Polytechnic. The method used was three treatment experiments, including installing a single pump, a series pump installation, and a parallel pump installation. Observed changes are flow rate, water pressure, motor rotation, and electric current. The results showed that the series pump did not affect the discharge, but it affected the pressure and hydraulic power of the pump. While the parallel pump affects the increase in discharge but does not affect the pump pressure and hydraulic power. The results of pump calculations flow rate series 0.000450 m3 / sec, while the parallel pump flow rate 0.000769 m3 / sec. The results of pump measurement pressure are 80 psi series, while the parallel pump pressure is 40 psi. The calculation result of the hydraulic pump is 248.28 Watt series, while the parallel pump hydraulic power is 198.2 Watt. The power efficiency of series pumps is higher than the efficiency of parallel pumps. The efficiency of electric power when measuring flow rate at 70.53% series pump installations, parallel pump electrical power efficiency of 56.3%. The efficiency of electric power when measuring series water pressure is 45.14%, while the parallel pump's electrical power efficiency is 36.03%. Keywords: Efficiency, pump installation, series, parallel.